Teacher empathy and students with problem behaviors: Examining teachers' perceptions, responses, relationships, and burnout - Wink, Mackenzie N.; LaRusso, Maria D.; Smith, Rhiannon L. (Psychology in the schools, 2021)
Managing students' problem behaviors in the classroom is a difficult challenge for many teachers. A teacher's ability to empathize with students' perspectives and life experiences could impact their approach to the student's problem behaviors; however, few previous studies examine teacher empathy. This study adapted an existing empathy measure to assess educators' cognitive and affective empathy for students. Participants were elementary school teachers ( N = 178) who reported on their levels of empathy and completed measures of teacher‐student relationships, student behaviors, and approaches to handling behaviors for their self‐reported most challenging student. Results indicated the adapted measure reliably assessed teachers' cognitive empathy and an affective form of empathy characterized as empathic distress (experiencing personal distress from others' distress). Teachers higher in cognitive empathy reported more positive mindsets about student behavior, greater competence in handling problem behaviors, increased use of effective problem‐solving strategies, greater relationship closeness, and lower levels of job burnout. Teachers high in empathic distress showed largely opposite findings, with more negative misbehavior mindsets, greater relationship conflict, less competence, fewer problem‐solving strategies, and higher job burnout. These findings have implications for supporting teachers to effectively intervene and build positive relationships with behaviorally challenging students.